A cohort study of the efficacy of the dienogest and the gonadotropin-releasing hormone agonist in women with adenomyosis and dysmenorrhea. (1st February 2022) - Ji, Miaomiao; Yuan, Ming; Jiao, Xue; Li, Qiuju; Huang, Yufei; Li, Jing; Wang, Guoyun
Abstract: Purpose: To study the efficacy and safety of the dienogest and the gonadotropin-releasing hormone agonist (GnRH-a) in symptomatic females with uterine adenomyosis. Methods: A total of 127 patients with adenomyosis with a chief complaint of dysmenorrhea were recruited. The first group received 2 mg of dienogest (DNG) daily, whereas the second group received goserelin acetate (GS) (3.6 mg/4 weeks) for 12 weeks. Outpatient follow-up was undertaken after 12 weeks. Results: Among 127 women, 56/63 (88.9%) patients completed the treatment in the DNG group, whereas 62/64 (96.9%) patients completed the treatment in the GS group. A significant decrease in dysmenorrhea symptoms as measured by the visual analog scale (VAS) and Carcinoma antigen125 (CA125) after 12 weeks of treatment was observed in both groups ( p  < .001). The hemoglobin of anemic patients did not significantly improve after 12 weeks of treatment ( p ＝0.21) and the uterine volume slightly increased without statistical significance ( p ＝0.10) in the DNG group. Simultaneously, The hemoglobin of anemic patients significantly improved ( p  < .001) and the uterine volume significantly decreased ( p  < .001) in the GS group. Conclusions: Dienogest effectively alleviates the symptoms of dysmenorrhea in patients with adenomyosis, but it cannot improve the anemia or reduce the size of the uterus. GnRH-a is more effective in improving anemia and reducing the uterine volume in patients with adenomyosis. TRIAL REGISTRATION: ChiCTR1900024958